The absorption, distribution, metabolism and excretion of procyanidins. Issue 3 (27th January 2016) - Zhang, Liang; Wang, Yijun; Li, Daxiang; Ho, Chi-Tang; Li, Junsong; Wan, Xiaochun
Abstract : This review summarizes research on the in vivo and in vitro ADME of procyanidins (PAs), including the degradation of PAs in gastric digestion, their absorption in the small intestine and the pathway of their metabolism by colonic microflora. A systematic comparative analysis of published data is performed to elucidate the pharmacokinetics of PAs in vivo . Abstract : Procyanidins (PAs) are polyphenols in plant food that have many health benefits, including cancer prevention, cardiovascular protection and diabetes prevention. PAs have been known to have low oral bioavilability. In this review, we summarize the published results on the ADME (absorption, distribution, metabolism and excretion) of PAs in vivo and in vitro . After oral administration, in the stomach the decomposition of PAs is highly dependent on the pH value of gastric juice, which is also affected by food intake. In the small intestine, PA polymers and oligomers with DP > 4 are not directly absorbed in vivo, but minor PA monomers and dimers could be detected in the plasma. Methylated and glucuronidated PA dimers and monomers are the main metabolites of PAs in plasma. In the colon, PAs are catabolized by colonic microflora into a series of low molecular weight phenolic acids, such as phenyl valerolactone, phenylacetic acids and phenylpropionic acids. We reviewed the degradation of PAs in gastric digestion, the absorption of PAs in the small intestine and the metabolic pathway of PAs by colonic microflora. To clearly explain the in vivo pharmacokinetics of PAs, a systematic comparative analysis on previously published data on PAs was conducted.